Effects of the FIFA 11+ on injury prevention in amateur futsal players. (4th May 2020) - Lopes, Mário; Simões, Daniela; Costa, Rui; Oliveira, José; Ribeiro, Fernando
Abstract : Objective: To examine the effectiveness of the FIFA 11+ in reducing injury in futsal players. Methods: Ninety‐one male futsal players from six amateur futsal clubs were recruited and assessed for eligibility, and 71 were randomized to the 11+ group (n = 37, age: 27.0 ± 5.1 years) and a control group (n = 34, age: 26.0 ± 5.1 years). The 11+ program was executed twice a week for 20 weeks, separated by a 10‐week period where both groups executed their regular warm‐up. Data on match, training exposure, and injuries were recorded during the regular season. Results: The players sustained a total of 58 injuries during the futsal regular season, with 24 injuries in the 11+ group and 34 injuries in the control group; the overall incidence of injuries per 1000 player‐hours was significantly higher in the control group (11.6 vs 6.5; mean difference (95% CI) −5.1 (−9.1 to −1.1), P = .014). The 11+ group had a significantly lower incidence of acute (11.2 vs 5.7; −5.5 (−9.4 to −1.6), P = .007) and lower limb (8.7 vs 4.4; −4.2 (−8.1 to −0.4), P = .032) injuries per 1000 player‐hours. Players from the control group had a higher number of days injured (20.4 ± 17.3 vs 10.5 ± 9.1, P = .036). Conclusion: The FIFA 11+ is an injury prevention program suited for injury reduction in amateur futsal players, as it reduces the incidence of overall, acute, and lower limb injuries during the season.